Physical habitat quality and interspecific competition interact to influence territory settlement and reproductive success in a cavity nesting bird - Jones, John A.; Harris, Morgan R.; Siefferman, Lynn (Frontiers in Ecology and Evolution, 2014)
Determining how to best measure habitat quality is essential for many conservation plans and basic ecological questions. Territory quality is thought to be a product of physical habitat characteristics (i.e. habitat quality) and the density of competitors yet these relationships are rarely demonstrated. Occupancy rates, or how often a territory has been used since its establishment, are often used as a proxy for habitat quality. We tested the utility of occupancy rates as a proxy of habitat quality by comparing it with reproductive output in eastern bluebirds (Sialia sialis). We then tested the extent to which occupancy rates are influenced by physical habitat quality (land cover via remote sensing), aggressive interspecific competition with tree swallows (Tachycineta bicolor), and the individual quality of the breeding birds. We found that occupancy was the best predictor of reproductive output although female age and habitat openness also contributed to reproductive success. Habitat openness and competition with tree swallows best predicted site occupancy. Bluebirds appeared to avoid settling in areas of higher interspecific competition with tree swallows, but when bluebirds settled in areas of higher interspecific competition, physical (spatial) habitat quality was a good predictor of settlement location. Thus, our results suggest that although historical occupancy of territories is an accurate and easy-to-measure proxy of reproductive output, the realized habitat quality is a product of the tradeoffs between spatial habitat quality and interspecific competition. Here, we show that aggressive interspecific competition interacts with spatial habitat to influence settlement. A better understanding of how these variables influence settlement and productivity may better enable the management of source, rather than sink, habitats.